Health and markets: Universal beef issues - McReynolds, Sara (My University, 2008)
To complete my combined veterinary and public health (DVM/MPH) degree requirements, I spent 12 weeks (June 1, 2008 to September 1, 2008) working in South America on animal and human health issues along with Joan Talbott, DVM / MPH candidate. The field of veterinary medicine is very closely linked to public health. My area of interest in public health is infectious diseases and zoonoses so I chose to work with the USDA for my field experience. Dr. David Ashford, DVM, MPH, DSc, Assistant Area Director, USDA-APHIS, IS agreed to be our field supervisor. The overall goal was to gain knowledge of the job responsibilities and career pathways for veterinarians in public service and public health, and the specific roles and responsibilities of these agencies. First Goal The first goal of my experience was to increase awareness of the specific differences and challenges of eradication versus control programs in developing countries, the design and implementation of intensive national health programs, and the details of Foot and Mouth disease and epidemiology. The project included training and experience in outbreak investigation, GIS, surveillance, and the epidemiologic methods of cross-sectional serologic studies. Second Goal The second goal of my experience was to study the role of relevant governmental and non-governmental organizations in animal and human health (the National Ministries, the Animal and Plant Health Inspection Service, the World Health Organization, the US Agency for International Development, other agencies in the Department of State, and Peace Corps).
Keywords: Beef exports; International markets; SENACSA; Universal beef issues; Health and markets; Paraguayan beef; Agriculture, Animal Culture and Nutrition (0475)